2017
DOI: 10.1021/acs.jmedchem.6b01317
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Competitive and Noncompetitive Ligands of the Organic Cation Transporter 1 (OCT1; SLC22A1)

Abstract: Organic cation transporter 1 (OCT1) plays a critical role in the hepatocellular uptake of structurally diverse endogenous compounds and xenobiotics. Here we identified competitive and noncompetitive OCT1-interacting ligands in a library of 1780 prescription drugs by combining in silico and in vitro methods. Ligands were predicted by docking against a comparative model based on a eukaryotic homologue. In parallel, high-throughput screening (HTS) was conducted using the fluorescent probe substrate ASP+ in cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
79
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 58 publications
7
79
2
Order By: Relevance
“…pdf). Currently, novel molecular entities (NMEs) are tested for interaction with hOCT1 and hOCT2 expressed in epithelial cells to determine whether they inhibit uptake of a cationic model substrate that is applied at a micromolar concentration (Ahlin et al, 2008(Ahlin et al, , 2011Chen et al, 2017). This procedure has turned out to be insufficient because it was observed that the efficacy of inhibitors was dependent on the molecular structure of the employed substrate and was different when substrate concentrations far below their respective Michaelis-Menten constant (K m ) values were used for uptake measurements (Belzer et al, 2013;Thévenod et al, 2013;Yin et al, 2016;Minuesa et al, 2017;Gorboulev et al, 2018;Sandoval et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…pdf). Currently, novel molecular entities (NMEs) are tested for interaction with hOCT1 and hOCT2 expressed in epithelial cells to determine whether they inhibit uptake of a cationic model substrate that is applied at a micromolar concentration (Ahlin et al, 2008(Ahlin et al, , 2011Chen et al, 2017). This procedure has turned out to be insufficient because it was observed that the efficacy of inhibitors was dependent on the molecular structure of the employed substrate and was different when substrate concentrations far below their respective Michaelis-Menten constant (K m ) values were used for uptake measurements (Belzer et al, 2013;Thévenod et al, 2013;Yin et al, 2016;Minuesa et al, 2017;Gorboulev et al, 2018;Sandoval et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Organic cation transporters (OCTs) OCT1, OCT2, and OCT3 (SLC22A1-3) of the major facilitator superfamily MFS play pivotal roles in the absorption, excretion, and tissue distribution of many cationic drugs including psychopharmaca and cytostatics (Koepsell et al, 2007;Ahlin et al, 2008;Nies et al, 2011;Koepsell, 2013;Lin et al, 2015;Chen et al, 2017). The polyspecificity of OCTs explains their predominant role for drug bioavailability and the high probability for drugdrug interactions at the transporter level.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vitro testing of human OCT1 (hOCT1) for drug-drug interactions was recommended in 2015 by the European Medicines Agency. Although methods to identify new substrates and inhibitors of OCTs have been established, so far no satisfying strategies for in silico and/or in vitro distinction between substrates and inhibitors and for elucidation of biomedically relevant effects of transporter polymorphisms have been found (Koepsell, 2015;Chen et al, 2017). The reasons are that the transport mechanisms of OCTs are not fully understood, no crystal structures are available, and our molecular understanding of cation binding and translocation based on mutagenesis is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The organic cation transporter 1 (OCT1) mediates hepatic uptake of typically cationic substances with a molecular weight below 400 Dalton . In humans, OCT1 shows strong expression in the sinusoidal membrane of hepatocytes and only minor, if any, expression in other organs .…”
mentioning
confidence: 99%
“…Apparently, thiamine is not useful as a probe drug for OCT1 activity, but the high heritability, particularly of thiamine monophosphate, may stimulate further genomic research.The organic cation transporter 1 (OCT1) mediates hepatic uptake of typically cationic substances with a molecular weight below 400 Dalton. [1][2][3][4] In humans, OCT1 shows strong expression in the sinusoidal membrane of hepatocytes 5 and only minor, if any, expression in other organs. 6,7 OCT1 can be relevant for the hepatic uptake and pharmacokinetics of numerous drugs, including metformin, morphine, O-desmethyltramadol, sumatriptan, fenoterol, trospium, and ranitidine.…”
mentioning
confidence: 99%